Tiktok Use Intensity and Adolescent Cyberbullying: Emotional Intelligence as Moderator - Mahsun Arifandy; Zainul Anwar (Psychological Journal: Science and Practice, 2026)
The development of social media, especially TikTok, has changed the socialinteraction patterns of adolescents and increased the risk of cyberbullyingbehavior . High intensity of TikTok use allows adolescents to be morefrequently exposed to aggressive content, negative comments, andcommunication patterns that have the potential to normalize cyberbullyingbehavior . However, not all adolescents with high TikTok use show the sametendency for cyberbullying, so it is necessary to study the psychologicalfactors that may influence this relationship. This study aims to determine theeffect of TikTok use intensity on cyberbullying behavior in adolescents and toexamine the role of emotional intelligence as a moderating variable. Thestudy used a quantitative correlational approach involving 315 adolescentTikTok users aged 18–21 years who were selected using a purposivesampling technique. Data collection was carried out through the TikTok useintensity scale, the cyberbullying scale, and the emotional intelligence scale.Data were analyzed using moderation analysis through the Hayes process instatistical software. The results showed that TikTok use intensity has apositive effect on cyberbullying behavior in adolescents. In addition,emotional intelligence is known to play a protective role that can weaken therelationship between TikTok use intensity and cyberbullying behavior. Adolescents with higher emotional intelligence tend to be better able tomanage their emotions, control aggressive impulses, and avoid cyberbullyingbehavior in digital interactions . This research emphasizes the importance ofstrengthening emotional intelligence as a preventative measure to reduce therisk of cyberbullying in adolescent social media users.